Characteristics and outcomes in a prospective cohort of patients with histologically diagnosed aortitis. Issue 1 (25th January 2019) - Goldhar, Hart A; Walker, Kyle M; Abdelrazek, Mohamed; Belanger, Eric C; Boodhwani, Munir; Milman, Nataliya
Abstract: Objectives: Our aim was to evaluate characteristics and prospective adverse aortic outcomes in a cohort of patients with non-infectious histological aortitis. Methods: Patients with histological aortitis, diagnosed at the Ottawa Hospital after surgical repair of thoracic aortic aneurysms or dissections, consented to enrolment in a prospective observational cohort. Patients were assessed for an underlying inflammatory condition and followed prospectively with periodic clinical, laboratory and radiographic assessments. Aortic outcomes during follow-up included significant events, defined as new thoracic or abdominal aortic aneurysms, dissections, ruptures or other complications requiring aortic intervention, in addition to aortic branch ectasias, aneurysms and stenosis. Results: Sixteen patients with histological aortitis from surgical procedures performed between 2010 and 2017 were included; nine had idiopathic and seven had secondary aortitis. Idiopathic patients were more likely to have smoked (100 vs 43%, P = 0.02) and had more associated arch or descending aortic aneurysms on pre-operative baseline imaging compared with secondary aortitis (6 vs 0, P = 0.01). At the median 3.6 years of follow-up, eight patients (50%) had 10 significant aortic events. The incidence of aortic dissection was higher in the first year post-surgery, compared with subsequent years, whereas incident aneurysms occurred throughout follow-up. Elevated inflammatory markers during follow-up trended towards association with accumulation of severe aortic damage. Conclusion: This is the first reported prospective study in patients with histological aortitis. Within the limitations of a small cohort, we report a high incidence of aortic complications. Studies with a larger sample size and longer follow-up are needed to corroborate these findings.